The effects of matrix proteins on the aflatoxin M1 bioaccessibility and the Caco-2 intestinal transport - Tavares, A.M. (2014)
Mycotoxins are fungal natural contaminants commonly found in food products that cause severe effects in human health, especially children. The mycotoxins occur in a great variety of foods, and can form complexes with the food matrix with a significant impact on their bioaccessibility. The bioaccessible fraction of the food contaminant contributes to the effective internal exposure depending on the contamination level, food matrix and the way the food is contaminated (spiked or naturally). To our knowledge, until now no studies were performed to disclose the possible role of milk proteins in the bioaccessibility of aflatoxin M1 (AFM1), a mycotoxin commonly found in milk products. On behalf of a Short Term Scientific Mission within the Infogest COST action and of the project Mycomix (FCT, Portugal), a collaboration study between the National Health Institute Doutor Ricardo Jorge (Portugal) and Agroscope Liebefeld- Posieux (Switzerland) was established. The recently submitted harmonized in vitro digestion protocol2 was for the first time applied to study the bioaccessibility of AFM1 in artificially contaminated infant formula and the protein profile of the samples analysed by LC-MS/MS. The results revealed a good performance of the harmonized method, showing a successful digestion of the proteins into smaller peptides. However, the presence of aflatoxin M1 contamination was not detected before and after digestion, suggesting an interaction with the food matrix. Moreover, in the transport assays, the presence of AFM1 did not impair the Caco-2 cells membrane integrity as shown by the Transepithelial Electrical Resistance. Further assays including an optimized AFM1 extraction method are in progress to evaluate toxin bioaccessibility and its presence in basolateral, apical cell media and cell cytoplasm.